Influence of vegetation physiognomy, elevation and fire frequency on medium and large mammals in two protected areas of the Espinhaço Range - Fernando Ferreira de Pinho; Guilherme Braga Ferreira; Adriano Pereira Paglia (Zoologia (Curitiba), 2017)
ABSTRACT The objectives of this study were to determine the richness of medium and large mammal species in two protected areas of the Espinhaço Mountain Range, state of Minas Gerais, Brazil; and to investigate the factors affecting the occurrence of those species. To accomplish that we placed 49 camera traps activated by heat and motion at Rio Preto State Park (RPSP) and 48 at Sempre Vivas National Park (SVNP). We also collected data on three environmental variables: vegetation physiognomy, elevation and wildfire frequency, to evaluate the influence of these factors on species richness and use intensity (inferred from camera trap detection rate) by large mammals. We recorded 23 large mammal species in the two parks combined. The lowest species richness was found at the rupestrian habitat of RPSP, and in the open grasslands of SVNP. The forest and savannah physiognomies were used more intensively by large mammals. Species richness was higher and use was greater at lower elevations of RPSP. In SVNP, fire frequency did not affect species richness or use intensity. The savannah habitat had very similar richness compared to the forests of the two protected areas. The high species richness and use intensity observed in these forest habitats highlights the importance of riparian environments in the Cerrado biome. The highest species richness and use intensity observed at low elevation follows patterns found in the literature, probably due to variation in the vegetation, which results in greater resource availability. Although rupestrian habitats at high elevations of the Espinhaço Range are known to have a high degree of endemism for some taxa, large mammal richness and use were not high in this habitat. These results indicate that the protection of native vegetation at lower elevations is crucial for the long-term conservation of large mammals in the Espinhaço Range.